Number 9 (November 1979) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1979)
The Status of the Southern Redbelly Dace, Chrosomus erythrogaster in Mississippi. By R.C. Cashner, et al., plus News Notes, 5 pp.
Keywords: southern redbelly dace; Chrosomus erythrogaster; mississippi